KINERJA BIDANG BINA MARGA PADA DINAS PUPR-PKPP PROVINSI RIAU DALAM PERBAIKAN JALAN PROVINSI DI KABUPATEN ROKAN HULU - Lisna Triwanti Zebua; Zaili Rusli (Universitas Halu Oleo, 2022)
The road maintenance division at the PUPR-PKPP Office of Riau Province is a government agency that is authorized and responsible for repairing provincial roads throughout Riau Province, one of which is Rokan Hulu Regency. Rokan Hulu Regency has 504 km of provincial roads with a total road damage of 117.99 km. Road damage in Rokan Hulu Regency has experienced many complaints from the public, so that the community considers the Bina Marga Division at the PUPR-PKPP Office of Riau Province to ignore road damage in Rokan Hulu Regency. The purpose of this study was to determine the performance and obstacles of the Highways Sector in repairing provincial roads in Rokan Hulu Regency. The research method used is qualitative research with descriptive analysis. The data needed are primary and secondary data derived from observations, interviews, and documentation which are analyzed by researchers so as to obtain accurate and clear data. The results of this study indicate that the performance of the Bina Marga Sector in carrying out road repairs in Rokan Hulu Regency is good, but there are several obstacles in the implementation of the work, namely the lack of APBD funds to carry out repairs and natural factors that can hinder the implementation of the road repair program